THE EFFECT OF EMPLOYEE ENGAGEMENT, WORKLOAD, AND SELF-AWARENESS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AMONG MEMBERS OF THE CIVIL SERVICE POLICE UNIT IN PAKPAK BHARAT REGENCY - Loide Astrike Banurea; Yanita; Aiyub; Nurmala (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study investigates the influence of employee engagement, workload, and self-awareness on organizational citizenship behavior (OCB) at the Civil Service Police Unit of Pakpak Bharat Regency. A quantitative research method with a descriptive associative approach was applied. Data were collected using a questionnaire and analyzed through multiple linear regression. This research aims to explore how psychological and work-related factors contribute to voluntary employee behaviors that go beyond formal job responsibilities. The study highlights the importance of building strong employee engagement, managing workload effectively, and fostering self-awareness to support positive organizational behavior.